METTL3-driven m6A modification of lncRNA FAM230B suppresses ferroptosis by modulating miR-27a-5p/BTF3 axis in gastric cancer - Cui, Yejia; Pu, Meicen; Gong, Yanting; Li, Runchao; Wang, Xiaokang; Ye, Jinjun; Huang, Haohai; Liao, Dan; Yang, Yufeng; Yin, Aiping; Li, Jiale; Deng, Yuling; et al. (Biochimica et biophysica acta. General subjects, 2024)
Our previous research revealed the apoptosis-inhibiting effect of lncRNA FAM230B in gastric cancer (GC). While its role on ferroptosis of GC remain unexplored. In this study, the m6A level and RNA stability regulation of METTL3 on FAM230B was detected by m6A quantification, stability assays, MeRIP, and their interaction was confirmed by RIP, and RNA pull-down assays. The level of ferroptosis was detected by flow cytometry, MDA and GSH level assessments, and electron microscopy. Gene expression was detected by quantitative real-time PCR, western blot, and immunofluorescence. The miR-27a-5p and BTF3 interaction was predicted with TargetScan and confirmed by dual-luciferase assay. Here, elevated levels of METTL3 and FAM230B were observed in GC tissues and cell lines. METTL3 was confirmed to bind with FAM230B RNA. Furthermore, silencing METTL3 reduced FAM230B m6A levels and stability, leading to decreased FAM230B and increased miR-27a-5p expressions. FAM230B knockdown favored ferroptosis and increased BTF3 expression, while its overexpression mitigated erastin-induced ferroptosis in GC cells. Additionally, BTF3 overexpression was found to negate miR-27a-5p's ferroptosis-promoting effects in GC cells. Collectively, our study demonstrates that the m6A modification of FAM230B by METTL3 plays a crucial role in promoting GC progression by reducing ferroptosis, through the modulation of the miR-27a-5p/BTF3 axis. •METTL3 and FAM230B are high-expressed in gastric cancer•METTL3 binds to FAM230B and up-regulates its m6A modification, therefore increases FAM230B stability•FAM230B inhibits GC cells ferroptosis by regulating miR-27a-5p/BTF3